Copyright Protection of Scientific Works using Digital Watermarking by Embedding DOI QR Code - Harahap, Muhammad Khoiruddin; Khairina, Nurul (Journal of Computer Networks, Architecture and High Performance Computing, 2021)
Digital identifier is a technology used to prove ownership of a work. At this time, the Digital Object Identifier is a form of implementation of the digital identifier used in every scientific work. Not infrequently there are several cases of theft of ownership or copyright of a work, both scientific works, and certain other works. Watermarking is a technique created to protect the ownership of works. Watermarking techniques can be applied to several media such as audio, video, and also documents, one of which is the Portable Document Format document file. In this study, researchers want to build copyright protection for scientific works. Researchers offer research concepts using a Digital Object Identifier which is always installed on scientific papers to be published. The Digital Object Identifier will later become the basic data in building the Quick Response Code. The Digital Object Identifier of each scientific work will not be the same as each other, this will certainly make the Quick Response Code more unique. The results show that the watermarking process in building copyright protection of scientific works can be very successful Quick Response Code can be read and detected properly without experiencing lag time. Quick Response Code readings from several variations of motion are also not very influential, so it can be concluded that distance does not limit the detection of Quick Response Codes. From this research, researchers can deduce that the watermark is performed on the scientific work not only serves as the copyright protection of that scientific paper but can also be an alternative for other researchers to access the scientific work.